Mathematics literacy on creative problem solving with realistic mathematics education approach assisted by e-learning schoology - Azmi, Anisa Luthifa; Wardono, Wardono; Cahyono, Adi Nur (Department of Mathematics, Universitas Negeri Semarang, 2018)
This research was conducted to find out the influence of Creative Problem Solving (CPS) model of learning with RME approach with the help of Schoology to increase junior high school students’ mathematic literacy and students’ learning output. This research used design true experimental design pretest-posttest control group design. This research used qualitative research method which involved control group and experiment group. The sampling technique used was random sampling. Experiment class was given a treatment in the form of Creative Problem Solving-RME learning. Meanwhile, control group was given a treatment in the form of expository-scientific. The data was collected using mathematic literacy’s ability test, observation, and interview. From the final data of mathematic literacy’s ability test, the researcher analysed and obtained that: (1) the students’ proportion in Creative Problem Solving-RME learning which passed the minimun criteria of mastery learning (KKM) was about 75%; (2) the average of students’ mathematic literacy on Creative Problem Solving- RME learning was better than the average of students’ mathematic litaracy on expository learning. So, we can conclude that Creative Problem Solving-RME learning was effective to improve students’ mathematic literacy.